2012
DOI: 10.1016/j.ijgo.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endometrial volume and vascularization using transvaginal 3D power Doppler angiography in women with postmenopausal bleeding

Abstract: 3D-PDA was not found better than 2D ultrasound at distinguishing benign from malignant disease in women with AUB and an endometrial thickness greater than 4.5mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…De plus, l'utilisation de THM, é lé ment inté gré à plusieurs modè les demeure une situation trè s peu fré quente dans notre pays. Quelques modè les sont é galement basé s sur une technique tridimensionnelle de l'é tude de l'endomè tre [16], technique non seulement non encore disponible dans notre pays mais aussi dont les ré sultats sont comparables à l'é tude bidimensionnelle en valeur pré dictive [16].…”
Section: Discussionunclassified
“…De plus, l'utilisation de THM, é lé ment inté gré à plusieurs modè les demeure une situation trè s peu fré quente dans notre pays. Quelques modè les sont é galement basé s sur une technique tridimensionnelle de l'é tude de l'endomè tre [16], technique non seulement non encore disponible dans notre pays mais aussi dont les ré sultats sont comparables à l'é tude bidimensionnelle en valeur pré dictive [16].…”
Section: Discussionunclassified
“…The morphologic features should be uniform and, if there are irregularities, or if the EEC cannot be adequately evaluated (Figure 4), other investigations are warranted, such as contrast sonography, hysteroscopy, and/ or endometrial sampling. At this time, available evidence suggests that there are no advantages offered by the use of 3-dimensional ultrasonography, as compared with standard 2-dimensional ultrasonography 62 (Class 3).…”
Section: Transvaginal Ultrasonographymentioning
confidence: 99%
“…A further 24 studies were excluded: two studies did not use the VOCAL method; 14 studies included only patients with previous diagnosis of carcinoma; four studies included premenopausal and postmenopausal women and data could not be stratified for menopausal status; in three studies it was not possible to retrieve data to make a 2×2 table to calculate true positive, true negative, false positive, and false negative cases; and one study was a retrospective study using the same data of another included study. The remaining eight [16][17][18][19][20][21][22][23] studies were ultimately included in the present meta-analysis. No additional studies from references cited in these eight studies were found.…”
Section: Search Resultsmentioning
confidence: 99%
“…With regard to the risk of bias for the patient selection domain, all studies were considered as having a high risk of bias. Six out of the eight studies included only women with a thickened endometrium, >4 mm; [17][18][19][20]22,23 three studies excluded patients with previous gynaecologic disease such as fibroids or polyps; 16,21,23 and one study pooled the hyperplasia with atypia and endometrial cancer in the same group. 16 Concerning the index test domain, all the studies used the VOCAL rotational method to calculate the endometrial volume.…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation